A tracked field study of thermal adaptation during a short-term migration between cold and hot-summer and warm-winter areas of China. (1st November 2017) - Liu, Yanfeng; Dong, Yu; Song, Cong; Wang, Yingying; Liu, Lulu; Liu, Jiaping
Abstract: The thermal adaptation of migrants is a continuous dynamic process which involves the adaptation of migrants to new thermal environment with their natural heat acclimation in original residence; however, this process has rarely been systematically investigated. This study explored whether the thermal comfort of migrants was significantly different from that of the local people during a short-term migration. Furthermore, whether the evolution of migrants' acclimation was developmental or reversible was also discussed. The survey was conducted in summer and included an adaptive investigation in Qionghai for eight days and a de-adaptation research in Xi'an for four days. Seven migrants who grew up in the northern China without any experiences of the southern lifestyle were recruited in a tracking field survey. The natural adaptation of the indigenes in Qionghai was also investigated as the control group. Comparison of indoor physical parameters and thermal subjective evaluation between the migrants and indigenes aided in systematical investigation of the time dependent adaptive level and preferred environment. The results showed that although thermal responses of migrants were significantly different from those of natives in the first and second day of migration, which then followed a trend similar to that of natives. Migrants were more sensitive and adaptive to high humidity environment. This study indicates that consideration of the thermal adaptive trend is definitely required when an indoor thermal environment is attempted to be designed for migrants. The results can be the basis of indoor environment design for migrants. Highlights: The adaptive and de-adaptive progresses of migrants were daily surveyed. The hallmark and characteristics of short-term adaptation were discussed. The adaptabilities of migrants and natives were fundamental different. Migrants were more adaptive to humid sensation than thermal sensation. Migrants were in primary stage of thermal adaptation in an eight-day travel.